THE ROLE OF POETRY IN TEACHING CHILDREN A FOREIGN LANGUAGE AND ITS ADVANTAGES IN THE DEVELOPMENT OF PRONUNCIATION - Gulchiroy Radjabova Gayrat kizi (PEDAGOGS, 2024)
Abstract: This article examines the role of poetry in teaching children a foreign language and its advantages in the development of pronunciation. The study examines the effects of incorporating poetry into language teaching to improve pronunciation skills among young language learners.